Change of the structure of the surface of galvanic coatings under exposure to cold air plasma - A. G. Anisovich; I. I. Filatova; S. V. Goncharik; V. F. Gologan; Zh. I. Bobanova (Литьë и металлургия)
Methods of metallographic analysis and scanning probe microscopy are used to study changes in the surface of copper electroplating under the influence of cold air plasma. At research in an optical microscope changes of structure of a surface are not established. The change in the surface relief is noticeable in the transverse section when examined by the method of sighting metallography. Scanning probe microscopy revealed a change in the surface morphology – a reduction in roughness and smoothing of relief fragments. The established features can be essential for the development of methods for improving the wear resistance of electroplated galvanic coatings.